2014
DOI: 10.1007/s40429-014-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances: Implications for Cannabis Use, Cannabis Use Cessation, and Cannabis Use Treatment

Abstract: Cannabis may be used, among certain individuals, for its actual and/or perceived sleep-promoting properties. Although evidence suggests that cannabis is likely beneficial for sleep initiation, over time individuals may develop tolerance to these benefits, leading to greater use in order to maintain the same sleep-inducing effects. This form of use likely contributes to the development of problematic cannabis use patterns, including cannabis use disorders. Evidence also points to sleep as an important considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 66 publications
(69 reference statements)
2
28
0
Order By: Relevance
“…In conjunction with prior empirical work, findings are consistent with a model whereby individuals with PTSD find cannabis to be a useful short-term coping strategy to reduce acute symptoms (e.g. poor sleep) (42). However, coping-oriented use among this population may lead to dependence and exacerbated symptoms of withdrawal and craving during cessation attempts (13,34).…”
Section: Discussionsupporting
confidence: 80%
“…In conjunction with prior empirical work, findings are consistent with a model whereby individuals with PTSD find cannabis to be a useful short-term coping strategy to reduce acute symptoms (e.g. poor sleep) (42). However, coping-oriented use among this population may lead to dependence and exacerbated symptoms of withdrawal and craving during cessation attempts (13,34).…”
Section: Discussionsupporting
confidence: 80%
“…Although evidence suggests that cannabis is likely beneficial for sleep initiation, tolerance may develop over time, potentially leading to cannabis use disorder. Again sleep disturbances are a primary symptom of cannabis withdrawal, and may be a significant risk factor for relapse and abuse [82].…”
Section: Sleep Disordersmentioning
confidence: 99%
“…The rapidly changing epidemiology of medical cannabis highlights the importance of research on the potential beneficial and adverse effects of cannabis use (Volkow et al, 2017). Although a long line of research has established associations between recreational cannabis use and adverse health outcomes (Wilkinson et al, 2016), the relationship between cannabis use and sleep appears to vary as a function of dose and timing of administration (Babson and Bonn-Miller, 2014; Conroy and Arnedt, 2014). Evidence indicated that cannabis has sedative and excitatory effects (Babson and Bonn-Miller, 2014), and cannabis withdrawal is associated with sleep disruptions (Bolla et al, 2010; Gates et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although a long line of research has established associations between recreational cannabis use and adverse health outcomes (Wilkinson et al, 2016), the relationship between cannabis use and sleep appears to vary as a function of dose and timing of administration (Babson and Bonn-Miller, 2014; Conroy and Arnedt, 2014). Evidence indicated that cannabis has sedative and excitatory effects (Babson and Bonn-Miller, 2014), and cannabis withdrawal is associated with sleep disruptions (Bolla et al, 2010; Gates et al, 2016). One study showed that heavy (but not occasional) cannabis use was associated with sleep disturbance (Conroy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation